Anaerobic Process. (1st October 2017) - Huang, Fang; Ju, Mei‐Ting; Li, Wei‐Zun; Chang, Chein‐Chi
Abstract : This is a review of the literatures published in 2016 on the focus of Anaerobic Process. It is divided into the following sections.  Pretreatment  Organic waste  Multiple‐stage co‐digestion  Process Methodology and Technology